THE ACCOUNTING SYSTEM IN TRADE ORGANIZATIONS, AS WELL AS THE CLASSIFICATION OF INCOME IN TRADE - Yusupova Farizabonu Zarifovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article presents the boundary between trade organizations and their income items, as well as the possibility of showing the results of their various combinations and the activities of trade organizations. Accounts and descriptions of income from further financial and economic activities are highlighted.